Deglobalisation and Copyright Law - Mateusz TONDERA (Communications of International Proceedings, 2025)
This article examines how current deglobalisation processes reshape the architecture and purpose of intellectual property (IP) protection, particularly copyright law. Once at the forefront of globalisation, IP regimes have historically promoted the harmonisation of legal standards and facilitated the global flow of creative and technological goods. However, recent geopolitical, economic, and ideological shifts—intensified by the COVID-19 pandemic and the war in Ukraine—have disrupted these trends. The resulting fragmentation of international cooperation has led to a reorientation of IP policy toward national or bloc-specific interests. The paper identifies key manifestations of this trend, including divergent legal standards in the United States, the European Union, China, and Russia; increasing regulatory protectionism; and tensions over access to medicines, digital technologies, and data governance. These developments indicate that the once-dominant paradigm of globally unified IP protection is giving way to a pluralistic, interest-driven system reflecting broader transformations in the global order. The article argues that deglobalisation  does not halt the exchange of intellectual goods but redefines the values and power structures underpinning it. For legal scholars and practitioners, this shift entails both challenges and opportunities: navigating a landscape marked by competing normative foundations, varying degrees of state intervention, and the growing instrumentalisation of IP law as a tool of economic and political strategy.
Keywords: Deglobalisation; copyright law; intellectual property; globalisation; legal fragmentation